Detecting cortical microstructural alterations secondary to white matter hyperintensity in amyloid positive cognitively normal subjects - Torso, Mario; Ridgway, Gerard R; Valotti, Michele; Hardingham, Ian; Chance, Steven A (Alzheimer's & dementia, 2023)
Background Previous research showed that cortical diffusivity is sensitive to primary cortical microstructural changes due to amyloid deposition (1). The present study aimed to investigate the cortical microstructural alterations secondary to white matter damage in cognitively normal participants, amyloid positive and negative. Method Three hundred and thirty‐five cognitively normal (MMSE > 24) participants with baseline CSF Aß42 and MRI scans were obtained from the European Prevention of Alzheimer’s Dementia (EPAD) cohort. Participants were classified as Aß42‐ (N = 231) or Aß42+ (N = 104), based on a published cut‐off (2). The Fazekas scale deep white matter (FSDWM) score was used to further classify participants as LOW (0 and 1; N = 281) or HIGH (2 and 3; N = 54) FSDWM. Structural and diffusion MRI (dMRI) were used to calculate whole brain cortical volume fraction, cortical thickness and three neuropathology‐inspired cortical diffusivity measures: the angle between the radial minicolumnar direction and the principal diffusion direction (AngleR); the principal diffusion component parallel with the minicolumns (ParlPD), and the diffusion components perpendicular to the minicolumns (PerpPD+). Group differences in structural and diffusion metrics were tested using GLM adjusting for scanner manufacturer, number of dMRI volumes, age and sex, with Bonferroni’s correction (p<0.05/5). Result The interaction between Aß42 status and FSDWM revealed significant differences in cortical microstructural measures (GLM: AngleR F17,317 = 7.065, p = 0.008; PerpPD+ F17,317 = 7.976, p = 0.005). The pairwise comparisons showed significantly lower AngleR values in Aß42‐ HIGH compared to Aß42‐ LOW and significantly higher PerpPD+ values in Aß42+ HIGH compared to Aß42+ LOW (Figure). No significant differences in structural measures (thickness or volume) were detected. Conclusion Cortical diffusivity measures can detect differences in cortical microstructure of amyloid positive and negative participants with different WM damage severity. The reduced AngleR value in Aß42‐ HIGH participants was potentially due to neuroinflammatory processes, consistent with previous findings(1). The higher PerpPD+ values in Aß42+ HIGH may indicate the secondary cortical microstructural damage. References: (1) Torso et al. 2022, PMID:36281682 (2) Ingala et al. 2021 PMID:33811742